Sistem Informasi Penerimaan Siswa Baru Pada Madrasah Tsanawiyah Nurussyafa’ah Bogor Menggunakan Framework Codeigniter - Hady Suwito, Helmi Yoga, Dwi Susanto (Sekolah Tinggi Ilmu Komputer El Rahma, 2023)
Abstract - The aim of this study is to create a new student admission information system software on the madrasah tsanawiyah nurussyafaah bogor built using the CodeIgniter framework to help operators in managing the new student admissions process more effectively and efficiently. Software development methods used are Rapid Application Development (RAD) and Unified Modeling Language (UML) as system documentation models. Software testing is carried out through black-box testing. Data in this study is collected using observation techniques, interviews, and literature studies. The results of the research showed that the new student admission information system on the nurussyafaah gymnasium developed in hope can help operators and users in managing the process of new student admissions effectively and efficiently. Keywords - Information System, new student Admission, Codeigniter, RAD